Identification of Biofilm-Producing Isolates of Pseudomonas aeruginosa Isolated from Wound Infections (Journal of the College of Basic Education, 2025)
Pseudomonas aeruginosa (P. aeruginosa) is the one of the most prevalence pathogenic bacteria especially in hospitals, and it is the most common bacteria causing wound infections. One of the most significant virulence factors it produces is biofilm, as it contributes to antibiotic resistance and persistent infections. The current study aims to detect biofilms formation for P. aeruginosa isolates collected from wound patients. A total of 51 isolates were obtained from 121 clinical sample of wound patients from different hospitals in Baghdad city, all isolates were submitted for cultural and biochemical tests for identification, then by using VITEK 2 system, all isolates were confirmed as P. aeruginosa. Biofilm production was detected by microtiter plate (MTP) assay, according to the results, (17.64%) of the isolates were weak biofilm producers, (50.98%) were moderate, and (31.37%) produced strong biofilm. The results of this study revealed that all isolates showed a highly proportional capacity to form biofilm, biofilm is the most important virulence factor of P. aeruginosa and has a significant effect on chronic wounds and affects the wound healing process. Therefore, it is necessary to develop new strategies to eradicate it.